DISTRIBUTION AND ABUNDANCE OF ECTO AND ENDO HELMINTH PARASITES OF Clarias gariepinus FROM NATURAL AND ARTIFICIAL HABITATS IN ANAMBRA STATE, SOUTHEASTERN NIGERIA. - I. O. Nnatuanya; B. A. Ugwumba; C. O. Ishar; E. C. Obijiofor; O. A. Okeke; C. C. Nwadike; I. M. Ikeh; C. O. Aniefuna; P. I. Afoemezie; N. P. Udeh (The Bioscientist)
Helminth parasites have been recognized as a major threat to fish health and cause reduced economic gains worldwide. This study aimed to determine the abundance and distribution of ecto and endo helminth parasites of Clarias gariepinus from natural and artificial habitats in Anambra state, Nigeria. A total of 40 live adult Clarias gariepinus (15.67–440.08 g body weight) were randomly purchased and examined for ecto and endo helminth parasites. The fish consists of 15 each from natural and 10 from artificial habitats. Standard parasitological techniques were used for the isolation and identification of the ecto and endo helminth parasites. Data obtained was analysed with ꭓ2 at 5 % significance level. Nineteen (48%) of Clarias gariepinus sampled were infected with 59 different species of helminth parasites. Endoparasites identified were: Procamallanus sp. (25%), Camallanus sp. (37.5%), Polyonchobothrium sp. (7.5%), and Protocephalus sp. (2.5%) with one ectoparasite Gyrodactylus sp. (2.5%) (P < 0.05). Natural and artificial habitats have a prevalence of 48% and 0% (P < 0.05) respectively. Catfish obtained from Otuocha section of Omambala River habitat with body weight 100-199g, has the highest prevalence (75%), while highest parasite distribution in organs was found in the intestines (40.0%). The higher infection rate observed among natural habitat fish indicates river contamination. Good hygienic practice is advocated among the community members.